Towards an analytical strategic environmental assessment: The ANSEA Network - Rodrigo Jiliberto; Manuel Alvarez-Arenas; Mercedes García; Cesar Cuevas; Anna McGillivray; Olivia Bina; Marialuisa Tamborra; Pietro Caratti; Riccardo Tarquini; Maria Rosario Partidario; Gustavo Vicente; Rafael Escribano; et al. (Fondazione Eni Enrico Mattei (FEEM), 2002)
The objective of the Analytical Strategic Environmental Assessment method is to provide a complementary and decision-centred approach to the SEA process. The focus is to evaluate the decision-making process instead of the quantitative output of an assessment. Thus, the project provides a methodology and the relevant tools to analyse and assess the decision-making process of policies, plans and programmes (PPP). By considering the whole decision-making process, decisions most critical to the environmental impact of PPP can be identified. The ANSEA approach is designed to be used as an objective and transparent approach to ensure that environmental considerations are taken into account, or as an evaluation of how far environmental integration has been achieved in decision making processes.
Keywords: O20; Q20; 330; Environmental Assessment; Impact Assessment; Strategic assessment; SEA; SIA; EIA; DM Planning; decision-making; Strategic Environmental Assessment